2016
DOI: 10.1002/gps.4542
|View full text |Cite
|
Sign up to set email alerts
|

The survival and characteristics of older people with and without dementia who are hospitalised following intentional self-harm

Abstract: Dementia is associated with an increased risk of hospitalisation for self-harm in older people and worse outcomes. The high rate of coexistent mental health conditions suggests that interventions which reduce behavioural and psychological symptoms of dementia might reduce self-harm in people with dementia. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 24 publications
0
36
0
Order By: Relevance
“…Eleven studies had a small sample size (range: 42‐395), were conducted in a single hospital (‐ward), or showed a sex distribution not representative of the PWD population . Thirty‐three studies met the criteria for comparability based on design or analysis, thereof 8 studies controlled or matched for 1 factor and 25 studies for at least 2 factors . Fourteen studies reported multivariate and descriptive results for LOS, and 5 studies solely multivariate results .…”
Section: Resultsmentioning
confidence: 99%
“…Eleven studies had a small sample size (range: 42‐395), were conducted in a single hospital (‐ward), or showed a sex distribution not representative of the PWD population . Thirty‐three studies met the criteria for comparability based on design or analysis, thereof 8 studies controlled or matched for 1 factor and 25 studies for at least 2 factors . Fourteen studies reported multivariate and descriptive results for LOS, and 5 studies solely multivariate results .…”
Section: Resultsmentioning
confidence: 99%
“…The reported rates of all-cause 30-day readmission ranged from 7% 17 to 35%. 8,9,18,23,30,31 However, when comparing readmission rates between persons with dementia and persons with depression, no differences in readmission rates were found. 30 Two research teams studied condition-specific readmissions, including drug-related readmissions 26 and psychiatric readmissions.…”
Section: Readmission Ratementioning
confidence: 94%
“…17.8 and 18.9% in the United States,8,18 to 23.6% in Australia 31. This finding implies the influence of health care system and societal differences on patient outcomes, including readmission.Interestingly, none of the reviewed studies examined readmission rates based on where patients were readmitted from (eg, nursing home, home care agency, and home).…”
mentioning
confidence: 89%
See 2 more Smart Citations